A qualitative study into the advocacy and activism of carers of adolescents with Down Syndrome in Oshana, Namibia - Kambowe, Hannah (Department of Health and Rehabilitation Sciences, 2020)
Background: Down Syndrome (DS) is a chromosomal defect known to cause intellectual disability. Adolescents with DS may need to live with their families beyond the transition period into adulthood because they require lifelong care due to the disabling consequences of the genetic condition. Evidence is lacking about the actions that carers in remote rural communities are taking to enhance the rights of their adolescents with DS as enshrined in the United Nations Convention on the Rights of Persons with Disabilities (CRPD). Aim: To describe the advocacy and activism actions of carers that promote the disability rights of adolescents with DS. Objectives: To describe carers’ understanding of 'activism’ in relation to the needs of adolescents with DS; to explore what actions carers are engaging with in order to promote participation and equal opportunities for social inclusion of adolescents with DS; to describe barriers encountered and strategies used and to describe carers’ advocacy priority list for social inclusion of adolescents with DS. Methodology: A descriptive qualitative approach was used where three carers told their stories of activism and advocacy actions through a semi-structured in-depth interview method. Their stories were audio-recorded, transcribed into textual form and an inductive data analysis followed a framework approach guided by the research aims. Findings: One overriding theme Puuyelele (bringing adolescents with DS into the open) emerged with four categories: namely, “Speaking for and acting on behalf of adolescents with DS”, “Enabling a continuous enlightening process”, “Ensuring ongoing care and services” and “Raising public awareness on human rights of adolescents with DS”. Discussion: Three concepts about DS advocacy and activism for adolescents with DS formed the discussion; first, it is a strategic process requiring togetherness, courage and perseverance; second, it proceeds from vigilant care-giving and service provision and, lastly, it requires rising of human rights awareness. Conclusion: A strategic and contextualised DS advocacy and activism process such as Puuyelele requires human rights awareness and emerges from vigilant care that enhances community participation and social inclusion of adolescents with DS. The process creates a possible and realistic conceptual framework for further strengthening of disability-inclusive development initiatives in Namibia.